Stress Coping Mechanisms in the Lord’s Prayer: A Content Analysis - Ehusani, Richard (International Journal of Research in Interdisciplinary Studies, 2025)
The Lord’s Prayer is among the most recited passages in Christian liturgy, yet its specific stress-coping functions have not been systematically examined. This study employed qualitative content analysis to map each of the prayer’s eight petitions onto Lazarus and Folkman’s transactional coping categories (problem-focused, emotion-focused, and meaning-focused) and Pargament’s religious coping dimensions (positive spiritual reappraisal and divine support). Two independent coding processes resulted in high interrater reliability (κ ≥ .80) in assigning one or more coping codes per petition. Results revealed a multimodal coping script: meaning-focused reappraisal and acceptance featured in three petitions, problem-focused appeals in two petitions, emotion-focused relief in two petitions, and explicit spiritual coping in one petition. The sequential arrangement, shifting from tangible resource requests to emotional catharsis, cognitive reframing, and spiritual transcendence, parallels best-practice stress interventions and suggests that the Lord’s Prayer functions as a compact, ritualised manual for resilience. Implications include integrating these findings into spiritually informed stress-management programs in pastoral and clinical settings. Future research should experimentally test prayer-based interventions, explore the effects of cross-cultural translation, and assess physiological and long-term psychological outcomes.